Edukacja dzieci romskich oczami nauczyciela. Przestrzenie nieodkryte - Pakura, Monika (Postscriptum Polonistyczne, 2020)
The paper presents the educational situation of Romani children in Poland. It reflects on the actions of the Polish state contributing to the improvement of the process of educating Romani people. Referring to the subject literature and to experience in work with Romani children, the paper also indicates areas that require constant support and actions aimed at improving the quality of Romani education. Consequently, these considerations represent an analysis and an attempt to verify the practical manifestation of the Romani people’s attitude towards school and its actions in favour of children from the Romani ethnic minority.